2015
DOI: 10.3892/mmr.2015.3641
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor-γ agonist inhibits the mammalian target of rapamycin signaling pathway and has a protective effect in a rat model of status epilepticus

Abstract: Peroxisome proliferator-activated receptor γ (PPAR-γ) has a protective role in several neurological diseases. The present study investigated the effect of the PPAR-γ agonist, pioglitazone, on the mammalian target of rapamycin (mTOR) signaling pathway in a rat model of pentylenetetrazol (PTZ)-induced status epilepticus (SE). The investigation proceeded in two stages. First, the course of activation of the mTOR signaling pathway in PTZ-induced SE was examined to determine the time-point of peak activity, as refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 55 publications
3
23
0
Order By: Relevance
“…S10 ). PPARG gene expression is up-regulated in neurons in response to excitotoxicity and ischemia ( 62 , 63 ), and modulates the microglial response to injury ( 64 , 65 ). PPARG agonists improve neuronal and glial survival in a variety of animal models involving ischemia and inflammation ( 62 , 66 69 ) and it has been suggested that they provide clinical improvement in children with autism ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…S10 ). PPARG gene expression is up-regulated in neurons in response to excitotoxicity and ischemia ( 62 , 63 ), and modulates the microglial response to injury ( 64 , 65 ). PPARG agonists improve neuronal and glial survival in a variety of animal models involving ischemia and inflammation ( 62 , 66 69 ) and it has been suggested that they provide clinical improvement in children with autism ( 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of nutrient sufficiency, the mTOR pathway is activated when mTORC1 inhibits autophagy by phosphorylating the Unc-51 like autophagy activating kinase 1 complex, which is a promoter of autophagy (14). However, under nutrient starvation, opposite events lead to the elevation of autophagy levels and cytoplasmic contents are eliminated to generate energy for essential cellular activities (10). There has been controversy regarding autophagy-associated alterations following SE.…”
Section: Phosphorylation Of Pras40 Contributes To the Activation Of Tmentioning
confidence: 99%
“…Abnormal activation of the mTOR pathway in SE has been reported by previous studies. For instance, San et al (10) revealed…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of mTOR pathway is likely one the mechanisms by which KD mediates these effects (McDaniel et al, 2011), which also involves the activation of peroxisomal proliferator-activated receptor γ (PPARγ) (Simeone et al, 2017). PPARγ is also linked to the control of the circadian clock (Chen and Yang, 2014) and hence a target for epilepsy treatment (San et al, 2015). Indeed, KD has been used as an antiepileptic treatment for some patients with drug-resistant epilepsy, but the underlying mechanisms of the KD action are still largely unknown.…”
Section: Approaches For Resetting the Circadian Rhythmsmentioning
confidence: 99%